To study the endothelial dysfunction by brachial artery flow mediated dilatation in coronary artery disease patients - Chouhan, Mahendra; Mandloi, Sohan Singh; Kansal, Archana; Jatav, O. P. (International Journal of Advances in Medicine, 2017)
Background: Brachial artery flow mediated dilatation (BAFMD), assessed by high resolution ultrasonography, reflects endothelium dependent vasodilator function. BAFMD is diminished in patients with atherosclerosis and with coronary risk factors and improves with risk reduction therapy. Methods: Study was conducted on 50 patients of coronary artery disease from In-patients who were admitted in the Department of Medicine and 25 healthy control without cardiovascular disease risk factors. All patients having established CAD i.e. Acute coronary syndrome and past history of CABG/angioplasty were included in study. Those morbidly ill and patients with evidence of chronic inflammatory or malignant disease were excluded. Doppler ultrasound of brachial artery was performed in all of them to assess baseline lumen diameter and flow mediated dilatation (i.e. percent change in brachial artery diameter after occlusion cuff release). Patients were divided into two groups; first group was classified as those having BAFMD less than 7.5% and the second group consisted patients having BAFMD less than 10%. Results: Flow mediated dilatation in cases was 6.87±5.48% as compared to the control group in which it was 13.08±3.40% and was statistically significant (P value 0.000002). Brachial artery flow mediated dilatation was abnormal in 80% cases at a cut off value <10% significant abnormalities; i.e. BAFMD <7.5% was found in 66% patients. Conclusions: Endothelial function as assessed by FMD is significantly impaired in patient of coronary artery disease. Hence it may be used as an important screening tool in people having cardiovascular disease risk factors and may play as a crucial role in preventive cardiology.